High‐Throughput Screening: One‐Step Generation of a Drug‐Releasing Hydrogel Microarray‐On‐A‐Chip for Large‐Scale Sequential Drug Combination Screening (Adv. Sci. 3/2019). Issue 3 (6th February 2019) - Song, Seo Woo; Kim, Su Deok; Oh, Dong Yoon; Lee, Yongju; Lee, Amos Chungwon; Jeong, Yunjin; Bae, Hyung Jong; Lee, Daewon; Lee, Sumin; Kim, Jiyun; Kwon, Sunghoon
Abstract : The need for a robotic pipetting machine to manage several substances limits the accessibility of high‐throughput screening techniques for general researchers. In article number 1801380, Jiyun Kim, Sunghoon Kwon, and co‐workers report a method to generate a large‐scale heterogeneous drug‐releasing‐microarray via a "pipetting‐free" manner by self‐assembly of encoded drug‐laden microparticles on the array of microwells.